Effect of Fertilization on the Growth and Biomass of Acacia mangium and Eucalyptus hybrid (E. grandis x E. pellita) - Siregar Sabar Timbul Halomoan; . Wawan; . Adiwirman (UNIVERSITY OF LAMPUNG, 2015)
Effect of fertilization on the growth and biomass of Acacia mangium and Eucalyptus hybrid (E. grandis x E. pellita) on third rotation is still not well understood to support judicious application in large scale forest plantations. A field experiment aimed at understanding these questions was conducted in PT. Riau Andalan Pulp and Paper forest concession in Riau during 2011 to 2013. The experiment consisted of 2 trials based on species, each was arranged in a Randomized Completely Block Design with 5 replicates. Treatments for A. mangium were zero fertilizer, 23 and 70 kg P ha-1 and for E. hybrid zero fertilizer, 70 and 210 kg N ha-1. Biomass at 24 months was estimated using allometric equations with diameter at breast height (DBH) as predictor. Significant effects are: increased DBH and stand volume of both species and height of E. hybrid. Increased aboveground and root biomass, but decreased root:shoot ratio (R:S) of both species. There was no significant effect of luxury rates of P or N on all parameters in each species. Stem was the biomass component most increased by fertilization resulting in proportional changes in other components except bark. Fertilization increased total leaf area, leaf specific area and stem growth efficiency of both species. Luxury fertilizer rates reduced fertilizer efficiency in both species. [How to Cite: Siregar STH, Wawan and Adiwirman. 2015. Effect of Fertilization on the Growth and Biomass of Acacia mangium and (E. grandis x E. pellita). J Trop Soils 20: 157-166. Doi: 10.5400/jts.2015.20.3.157]